Taxonomy of the immature stages of Oxelytrum cayennense (Sturm, 1826) (Coleoptera: Staphylinidae: Silphinae) of forensic importance from Central Amazon, Amazonas, Brazil - Eurico Hummig-Neto; José Albertino Rafael; Luana Machado Barros; Ruth Leila Ferreira-Keppler (Revista Brasileira de Entomologia)
ABSTRACT Oxelytrum cayennense (Sturm, 1826) is a necrophagous and predator beetle species (Staphylinidae), commonly found on decomposing carcasses in the Amazon region. The morphology of the immature stages is described using optical and scanning electron microscopy (SEM), which can help to correctly identify the species and minimize errors in the PMI estimation. The results show eggs cream-white in color. Larvae campodeiform, flattened dorsoventrally, predominantly brown in color, in first and second instar the lateral expansion is whitish, while the third instar is whitish only in anterior margin of the lateral expansion, posterior margin being brown. Pupae white, exarate and adecticous.